2020
DOI: 10.1088/1361-648x/ab7f08
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties in itinerant ferromagnet SrRu1−x Ti x O3

Abstract: SrRuO 3 presents a rare example of ferromagnetism among the 4d based oxides. While the nature of magnetic state in SrRuO 3 is mostly believed to be of itinerant type, recent studies suggest a coexistence of both itinerant and localized model of magnetism in this material. Here, we have investigated the evolution of magnetic state in doped SrRu 1−x Ti x O 3 through studying the critical behavior using standard techniques such as, modified Arrott plot, Kouvel-Fisher plot and critical isotherm analysis across the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
(229 reference statements)
1
1
0
Order By: Relevance
“…Whereas the Crdoped samples exhibit R-H hysteresis and the hysteretic nature increases with Cr doping. The overall nature of the negative MR resembles fairly well with other established ferromagnetic Ruthenates [25,71,72]. Interestingly, a sharp jump in MR is noticed (for CRCO10 and CRCO15) much above the coercive field (switching field H s ∼ 44 kOe).…”
Section: Transport Measurementssupporting
confidence: 82%
“…Whereas the Crdoped samples exhibit R-H hysteresis and the hysteretic nature increases with Cr doping. The overall nature of the negative MR resembles fairly well with other established ferromagnetic Ruthenates [25,71,72]. Interestingly, a sharp jump in MR is noticed (for CRCO10 and CRCO15) much above the coercive field (switching field H s ∼ 44 kOe).…”
Section: Transport Measurementssupporting
confidence: 82%
“…22 As for Ru site, magnetic (Fe 3+ , Co 3+ , Ir 4+ , Tc 4+ , and Mn 3+ ) and nonmagnetic (Ti 4+ , Pb 4+ , and Ga 3+ ) element substitution has been investigated. 18,[23][24][25][26][27][28][29] Magnetic elements participate in existing interactions, whereas nonmagnetic elements directly disrupt the coupling of 4d orbitals of Ru 4+ to the 2p orbitals of O 2− . It was reported that 10% Cr-doped SRO can increase T C to 188 K. 30 And the enhanced T C is attributable to broaden bandwidth due to the hybridization between Cr 3d and Ru 4d.…”
Section: Introductionmentioning
confidence: 99%